Animasi Interaktif Ragam Kebudayaan Jawa Tengah Berbasis Android - Adjat Sudradjat; Ismi Amalia Hoerunisa; Rahdian Kusuma Atmaja; Rino Ramadan (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2021)
Indonesia has a variety of cultures. One of them is the typical culture of Central Java found on the island of Java. The culture of Central Java itself is very rich and diverse. But along with the times, many people today, especially the citizens of Central Java themselves, are less familiar with their culture. This study aims to create interactive animation as an interesting alternative media based on Android to introduce the cultural diversity of Central Java. The application is created using Adobe Animate CC and Adobe Photoshop. The author uses a descriptive method to describe the object of research, whose data is processed and made into a generally accepted formulation. As for software development, the author uses the waterfall method which has several stages, namely software requirements analysis, design, code generation, testing, and support. The result of the research is an Android-based interactive animation game that can increase people's understanding of the variety of cultures found in Central Java. Keywords: Interactive Animation, Central Java Culture, Android Apps